2020
DOI: 10.1016/j.jcpa.2020.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology of Canine Infectious Respiratory Disease Complex and Prevalence of its Pathogens in Europe

Abstract: The canine infectious respiratory disease complex (CIRDC) is an endemic worldwide syndrome involving multiple viral and bacterial pathogens. Traditionally, Bordetella bronchiseptica (Bb), canine adenovirus type 2 (CAV-2), canine distemper virus (CDV), canine herpesvirus (CHV) and canine parainfluenza virus (CPiV) were considered the major causative agents. Lately, new pathogens have been implicated in the development of CIRDC, namely canine influenza virus (CIV), canine respiratory coronavirus (CRCoV), canine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 107 publications
(156 reference statements)
2
38
1
Order By: Relevance
“…Historically, the most common pathogens associated with complex canine infectious respiratory disease have been CPIV, CAV-2, Bordetella bronchiseptica, Streptococcus equi subsp. zooepidemicus, Mycoplasma cynos, CaHV-1, CDV, CIV, and CRCoV [25]. In our study, we detected eight of 33 analyzed dogs presenting classical primary respiratory pathogens, and we also detected IgM for CCoV in four dogs (3/17 pathological dogs and 1/20 healthy dog).…”
Section: Discussionsupporting
confidence: 58%
“…Historically, the most common pathogens associated with complex canine infectious respiratory disease have been CPIV, CAV-2, Bordetella bronchiseptica, Streptococcus equi subsp. zooepidemicus, Mycoplasma cynos, CaHV-1, CDV, CIV, and CRCoV [25]. In our study, we detected eight of 33 analyzed dogs presenting classical primary respiratory pathogens, and we also detected IgM for CCoV in four dogs (3/17 pathological dogs and 1/20 healthy dog).…”
Section: Discussionsupporting
confidence: 58%
“…Moreover, in veterinary medicine the respiratory disease is rarely lethal in the pet dog population. A mortality rate of 1•2% due to respiratory disease (only 0•3% due to pneumonia) has been reported, 19,20 nevertheless in our study we found a mortality rate of 42•5% during follow-up without a clarified etiology. These dogs, with very aggressive lung diseases, showed a very similar appearance to those described for COVID-19 pneumonia in human medicine.…”
Section: Discussioncontrasting
confidence: 55%
“…zooepidemicus, Mycoplasma cynos, CHV-1, CDV, CIV, and CRCoV. 20 In our study, we detect eight of 33 analyzed dogs presenting classical primary respiratory pathogens, and we also detect IgM for CCoV in four dogs (3/17 pathological dogs and 1/20 healthy dog). In this regard, the presence of CRCoV is detected more frequently in dogs with mild clinical signs than in dogs with moderate or severe clinical signs, 5 therefore, we would rule out that it was the agent responsible for the severe respiratory pathologies in these three dogs.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Adenoviruses are very resistant in the environment, surviving several days at room temperature and several months at ≤4°C. Canine adenovirus 2 (CAdV-2) causes mild self-limiting infection of the upper respiratory tract and is a contributor to infectious tracheobronchitis (ITB) known as kennel cough (Greene, 2012;Day et al, 2020).…”
Section: Samenvattingmentioning
confidence: 99%